Association between the dysfunctions of the stomatognathic system and the disorders in the statics of the body - Odzimek, Martyna (Journal of Education, Health and Sport, 2022)
INTRODUCTION The stomatognathic system is a group of tissues and organs consisting of: the mandible, teeth (upper and lower), two temporomandibular joints, muscles, ligaments and numerous vessels: nerve, blood and lymph. We define the body posture as an individual, individual feature of each person, which is expressed by the figure. A defect of posture or a disorder of the body statics is any anomaly from the correct posture that may be congenital or acquired. OBJECTIVE The main aim of the study was to assess the relationship between dysfunctions of the stomatognathic system and disturbances in body statics. The research was conducted from January to February 2022 using the proprietary questionnaire, which was made available online (Google Forms). RESULTS At least one symptom of body statics disorders was noticeable in 77 people from the group of people with problems within the stomatognathic system (88,51%). Only 10 people with disorders of the masticatory system motor system did not report any postural abnormalities (11,49%). The results of the research show that there is a statistically significant relationship between the occurrence of dysfunctions within the stomatognathic system and disturbances in body statics (x2 = 28,11 > x2 = 22,4570,001;6 - statistically significant relationship, rc = 0,304 - average strength of the relationship). CONCLUSIONS The complexity of the issue shows that focusing on only one problem may not produce the measured therapeutic effects. Only comprehensive and properly planned treatment brings the maximum therapeutic effect.